2010
DOI: 10.1016/j.jcrs.2010.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Corneal shaping and ablation of transparent media by femtosecond pulses in deep ultraviolet range

Abstract: The solid-state femtosecond UV laser system seems an attractive alternative to the currently used ophthalmic argon-fluoride excimer laser system because of its small footprint, silent operation, and ability to generate femtosecond light pulses at both 1027 nm (suitable for flap creation) and 205 nm (corneal ablation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…In our previous work, we have shown that UV pulses produced as the fifth harmonic of a femtosecond Ytterbium doped laser enable highly accurate and predictable ablation on model materials, as well as on the corneas of enucleated porcine eyes. 17 The ablation threshold fluence with femtosecond pulses was similar to that reported for excimer lasers, which indicated that absorption was dominated by linear single photon process. 17 Our experiments, in which rabbit corneas were treated in vivo with femtosecond UV pulses, did not show any adverse effects that could be induced specifically by high peak intensity, and the healing responses were similar to those after excimer ablation.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In our previous work, we have shown that UV pulses produced as the fifth harmonic of a femtosecond Ytterbium doped laser enable highly accurate and predictable ablation on model materials, as well as on the corneas of enucleated porcine eyes. 17 The ablation threshold fluence with femtosecond pulses was similar to that reported for excimer lasers, which indicated that absorption was dominated by linear single photon process. 17 Our experiments, in which rabbit corneas were treated in vivo with femtosecond UV pulses, did not show any adverse effects that could be induced specifically by high peak intensity, and the healing responses were similar to those after excimer ablation.…”
Section: Introductionsupporting
confidence: 75%
“…17 The ablation threshold fluence with femtosecond pulses was similar to that reported for excimer lasers, which indicated that absorption was dominated by linear single photon process. 17 Our experiments, in which rabbit corneas were treated in vivo with femtosecond UV pulses, did not show any adverse effects that could be induced specifically by high peak intensity, and the healing responses were similar to those after excimer ablation. 18 To be able to compare the results of ablation due to the two lasers, we adjusted the average power of our femtosecond UV source to that of the excimer laser we had at our disposal.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have evaluated the parameters, safety, and performance of various UV femtosecond laser systems. [70][71][72] Due to the shorter wavelength, it has been proposed that UV lasers can create a more accurate focus with less energy per laser pulse. Hammer et al 73 present the results of a study of 25 porcine eyes and 15 rabbit corneas with a new 345 nm UV femtosecond laser.…”
Section: Ultraviolet Femtosecond Lasersmentioning
confidence: 99%
“…One procedure, photorefractive keratectomy (PRK; Wavelight EX 500, Alcon, Ft Worth, TX, USA), involves the use of an excimer laser to ablate the corneal stroma after epithelial debridement [ 1 ]. The successor to PRK is laser-assisted in situ keratomileusis (LASIK) in which an epithelial flap is created to ablate the underlying stroma [ 2 - 3 ]. Although many believe LASIK is a safer operative procedure with less corneal damage [ 4 ], surgeons argue that PRK improves visual acuity and prevents future development of ectasia [ 5 ].…”
Section: Introductionmentioning
confidence: 99%